O Judiciário como potencial reformador democrático: educação para a cidadania - Souza Júnior, René Bernardes de (2007)
The present study has been developed aiming at evaluating the democratic educational power of the Judiciary while a state organ, and justifying the understanding of a matching performance to the paradigm set in Brazil after the Federal Constitution in 1988. The hypothesis observed during this work development involved the existence or not of educational power in the Judiciary action, both processual and extra processual, the difference between education to the authoritarism and democracy, the possibility and manner of gradual activation of the national citizenship through the judicial performance. The used methodology tried to conciliate the idealism and pragmatism on evaluating reality, research and analysis of proper proceedings at the democratic ideal reach based on law, which involved the contemporary national and international reality study and the objectives established in the Constitution as a consensual Brazilian ideal. The compared study of the juridical systems, law and judicial organs allowed the proceedings and reform understanding and which plus they bring to the authoritarism/democracy, power/consensus relationship in the political relation between the people and the state apparatus, judicial proceedings and the Judiciary image. The result showed that the judicial process has its particular features for the democratic education, as long as it is adapted to the active participation and understanding of the legally protected and, widely, of the population in the law learning, specially the Constitution the way it is activated in the judicial decision and process and in their objectives. The study yet showed the need for the Judiciary becomes more active, more close, more accessible and transparent to the Brazilian people in order to really set the democratic legitimation of this organ and its components along with its performance, mainly the ones in charge of higher authority in the moment for checking the public organ decisions and acts constitutionality